Uncommon Variants in FLG2 and NOD2 Are Associated with Atopic Dermatitis in the Ethiopian Population - Sailan Wang; Julia K. Elmgren; Jesper Eisfeldt; Samina Asad; Marlene Ek; Kassahun Bilcha; Annisa Befekadu; Carl-Fredrik Wahlgren; Magnus Nordenskjöld; Fulya Taylan; Isabel Tapia-Paez; Maria Bradley (Elsevier, 2024)
Loss-of-function variants in the FLG gene have been identified as the strongest cause of susceptibility to atopic dermatitis (AD) in Europeans and Asians. However, very little is known about the genetic etiology behind AD in African populations, where the prevalence of AD is notably high. We sought to investigate the genetic origins of AD by performing whole-genome sequencing in an Ethiopian family with 12 individuals and several affected in different generations. We identified 2 variants within FLG2 (p.D13Y) and NOD2 (p.A918S) genes cosegregating with AD in the affected individuals. Further genotyping analyses in both Ethiopian and Swedish AD cases and controls revealed a significant association with the FLG2 variant (p.D13Y, P < .0013) only in the Ethiopian cohort. However, the NOD2 variant (p.A918S) did not show any association in our Ethiopian cohort. Instead, 2 previously recognized NOD2 variants (p.A849V, P < .0085 and p.G908R, P < .0036) were significantly associated with AD in our Ethiopian cohort. Our study indicates that the FLG2 and NOD2 genes might be important in the etiology of AD in Ethiopians. Additional genetic and functional studies are needed to confirm the role of these genes and the associated variants into the development of AD.